Mind Your Language: The Effects of Linguistic Ostracism on Interpersonal Work Behaviors. (February 2021) - Fiset, John; Bhave, Devasheesh P.
Business and demographic trends are conflating to bring language issues at work to the forefront. Although language has an inherent capacity for creating interpersonal bonds, it can also serve as a means of exclusion. The construct of linguistic ostracism encapsulates this phenomenon. Drawing on ethnolinguistic identity theory, we identify how linguistic ostracism influences two interpersonal work behaviors: interpersonal citizenship and interpersonal deviance. We conduct a set of studies that uses multisource data, data across time, and data from three countries. Our results reveal that linguistic ostracism was associated with the enactment of lower interpersonal citizenship behaviors and higher interpersonal deviance behaviors. We find that disidentification served as a mechanism to explain why linguistic ostracism resulted in interpersonal citizenship behaviors and interpersonal deviance behaviors. Furthermore, linguistically ostracized employees with low (vs. high) social self-efficacy engage in fewer interpersonal citizenship behaviors and greater interpersonal deviance behaviors. We discuss theoretical implications associated with the phenomenon of linguistic ostracism and the implications for managers working in linguistically diverse organizations.